THE EFFECT OF USING QR CODES TO INCREASE ALMS IN THE MOSQUE - Tri Utami; Ahmad Maulana; Nadya Salsabila Haqqoni (Universitas Airlangga, 2022)
Abstract Technological developments have brought many changes to various sectors of human life, one of which is in terms of financial transactions. In the past, Indonesian people used to use their money as a means of payment. Now there is an innovation that makes it easier for people to make more efficient transactions, namely non-cash payments via e-money. One example is taking advantage of financial technology developments by using the QR Code to give alms and spend in mosques. Indonesia has been named the most generous country in the world. This is an opportunity to use fintech to give charity. By utilizing QR Code technology in the charity box, you can increase the income of alms and infaq at the mosque. The data used are primary data through questionnaires distributed in the Jabodetabek area with a total of 100 respondents. While secondary data were obtained from various literature studies such as journals, books, articles, and internet sites that are relevant to this research. The purpose of this study is to find out how much influence the QR Code is used in the mosque for giving alms. It is hoped that the QR Code technology used in this mosque can increase the development and use of sharia fintech in Indonesia.